Approximate and Conditional Teleportation of an Unknown Atomic State Without Bell-State Measurement with Two-Photon Interaction - CHEN Chang-Yong (Communications in theoretical physics, 2006)
A scheme for approximately and conditionally teleporting an unknown atomic state via two-photon interaction in cavity QED is proposed. It is the extension of the scheme of Ref. [11] [Phys. Rev. A 69 （2004） 064302], which is based on Jaynes-Cummings model in QED and where only a time point of system evolution and the corresponding fidelity implementing the teleportation are given. In our scheme, the two-photon interaction Jaynes-Cummings model is used to realize the approximate and conditional teleportation. Our scheme does not involve the Bell-state measurement and an additional atom, only requiring two atoms and one single-mode cavity. The fidelity of the scheme is higher than that of Ref. [11]. The scheme may be generalized to not only the teleportation of the state of a cavity mode to another mode by means of a single atom but also the teleportation of the state of a trapped ion.